2013 IEEE 11th International Symposium on Applied Machine Intelligence and Informatics (SAMI) 2013
DOI: 10.1109/sami.2013.6480975
|View full text |Cite
|
Sign up to set email alerts
|

Summarizing the behaviour of complex dynamic systems

Abstract: This paper outlines a general method for summarizing the behaviour of complex dynamic systems inspired by Bayesian causal analysis. The method is universally applicable and often permits to cut the backward causal loops through which the analyzed variables seem to co-determine themselves due to the nonlinearity of the equations describing complex systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…This model was used in project EUSAS financed by 20 nations under the Joint Investment Program Force Protection of the European Defence Agency. Interested readers can refer to a detailed exposition with a motivating example given in [5,4]. Below we provide a brief summary of the model.…”
Section: Internal Dynamics Of Civilian Agentsmentioning
confidence: 99%
See 4 more Smart Citations
“…This model was used in project EUSAS financed by 20 nations under the Joint Investment Program Force Protection of the European Defence Agency. Interested readers can refer to a detailed exposition with a motivating example given in [5,4]. Below we provide a brief summary of the model.…”
Section: Internal Dynamics Of Civilian Agentsmentioning
confidence: 99%
“…In [4] we tried to answer the question whether, in a scenario with this model, indirect social influence of nearby people was more important than external events in shaping the civilian agents' behavior. The answer provided by the causal summary of the scenario indicated that external events were more important.…”
Section: Internal Dynamics Of Civilian Agentsmentioning
confidence: 99%
See 3 more Smart Citations